2013
DOI: 10.3109/00365521.2013.777470
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and natural history of potential celiac disease in adult patients

Abstract: PCD is not a rare form of CD. Having found no difference at all in age at diagnosis and clinical features between PCD and active CD could suggest that PCD is not a prodrome of CD but is a separate entity that can only subsequently evolve into active CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 17 publications
3
68
1
1
Order By: Relevance
“…6,7 Published literature on the natural history of PCD in adults is scarce. Biagi et al 8 recently report that there is maintenance of normal duodenal mucosal histology for many years, as well as spontaneous symptom resolution despite a gluten-containing diet (GCD), in a subset of adult patients with PCD; however, a randomized controlled trial from Finland suggests there is an unequivocal benefit of a gluten-free diet (GFD) in adult patients with PCD. 9 In the last decade, CD has been increasingly recognized in the predominant wheat-eating population of northern India.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Published literature on the natural history of PCD in adults is scarce. Biagi et al 8 recently report that there is maintenance of normal duodenal mucosal histology for many years, as well as spontaneous symptom resolution despite a gluten-containing diet (GCD), in a subset of adult patients with PCD; however, a randomized controlled trial from Finland suggests there is an unequivocal benefit of a gluten-free diet (GFD) in adult patients with PCD. 9 In the last decade, CD has been increasingly recognized in the predominant wheat-eating population of northern India.…”
Section: Introductionmentioning
confidence: 99%
“…47,[52][53][54] A recent randomized study also shows that apparently asymptomatic EMA-positive subjects seem to benefit from their serological screening and subsequent GFD, 55 thereby supporting earlier evidence from Dickey et al; 56 however, some authors have suggested that EMA positivity in individuals with normal mucosa constitutes a separate entity (potential CD), different from CD. 57 A strict GFD sets major limitations on daily life and it is expensive and difficult to maintain. 58,59 Furthermore, removal of gluten from baked products makes them less palatable than comparable products in the normal diet.…”
Section: The Gfd: ''That a Treatment Is Available''mentioning
confidence: 99%
“…Since poor orientation precluded TH analysis of 81 biopsies, 1994 duodenal biopsies were analysed with both DM and TH. A total of 654 patients were affected by CD (281 on a gluten-containing diet and 534 on a gluten-free diet—161 patients underwent duodenal biopsy on both diets), 39 by complicated CD, 36 by potential CD (ie, positive endomysial antibodies but architecturally preserved duodenal mucosa13), 14 by common variable immunodeficiency-associated enteropathy,14 13 by Whipple's disease, four by Crohn's disease, three by autoimmune enteropathy, three by eosinophilic gastroenteritis, two by olmesartan enteropathy, one by Behçet's disease; the remaining 768 patients were affected by functional disorders. A thorough clinical description of all these patients is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%